CEREBRAL AMYLOID ANGIOPATHY AND ALZHEIMER’S DISEASE - Ghiso, Jorge (2010)
Cerebral amyloid angiopathy (CAA) is increasingly recognized as a major contributor of Alzheimer’s disease (AD) pathogenesis. To date, vascular deposits and not parenchymal plaques appear more sensitive predictors of dementia. Amyloid deposition in and around cerebral blood vessels plays a central role in a series of response mechanisms that lead to changes in the integrity of the blood-brain barrier, extravasations of plasma proteins, edema formation, release of inflammatory mediators and matrix metalloproteases which, in turn, produce partial degradation of the basal lamina with the potential to develop hemorrhagic complications. The progressive buildup of amyloid deposits in and around blood vessels chronically limits blood supply and causes focal deprivation of oxygen, triggering a secondary cascade of metabolic events several of which involve the generation of nitrogen and oxygen free radicals with consequent oxidative stress and cell toxicity. Many aspects of CAA in early- and late-onset AD –the special preference of Aβ40 to deposit in the vessel walls, the favored vascular compromise associated with many Aβ genetic variants, the puzzling observation that some of these vasculotropic variants solely manifest with recurrent hemorrhagic episodes while others are mainly associated with dementia– await clarification. Non-Aβ cerebral amyloidoses reinforce the viewpoint that plaque burden is not indicative of dementia while highlighting the relevance of nonfibrillar lesions and vascular involvement in the disease pathogenesis. The lessons learned from the comparative study of Aβ and non-Aβ cerebral amyloidosis provide new avenues and alternative models to study the role of amyloid in the molecular basis of neurodegeneration.